EFFECTIVENESS OF ABDOMINAL STRETCHING EXERCISE AND PROGRESSIVE MUSCLE RELAXATION ON REDUCING THE INTENSITY OF DYSMENORRHEA IN ADOLESCENT GIRLS - Fatmawati, Lilis; Imroatus Sholihah , Nabellah (Universitas Airlangga, 2025)
Introduction: Abdominal exercises help reduce pain by increasing blood circulation to the abdominal region, reducing muscle spasms, and improving flexibility of the uterine muscles. Muscle relaxation progressively reduces muscle tension and stress, which can worsen menstrual pain. This combination significantly reduces dysmenorrhea intensity, increases comfort, and supports the quality of life among adolescent girls. This study aimed to determine the effectiveness of abdominal stretching exercises and progressive muscle relaxation on reducing dysmenorrhea in teenage girls in Meluntur Village. Methods: This study used a quantitative approach with a quasi-experimental design, namely a two group pre-test and post-test control group design. A sample of 24 respondents was divided into two groups. The abdominal stretching exercise intervention was carried out on the first to third day of menstruation for 15 minutes twice a day, morning and evening. Progressive muscle relaxation intervention was carried out on the first to third day of menstruation for 15-30 minutes with a frequency of once a day, in the morning. The dependent variable was pain intensity in dysmenorrhea as measured by a numerical measurement scale. Results: The Wilcoxon test results for the abdominal stretching exercise group showed a p value = 0.025 (α<0.05) and for the progressive muscle relaxation group p value = 0.046 (α<0.05). The Mann Whitney test results showed a p value = 0.660 (α <0.05), indicating that there was no difference in the decrease in dysmenorrhea after the two interventions, because both helped reduce the intensity of dysmenorrhea. Conclusions: Adolescent girls who experience dysmenorrhea can perform either of these interventions.